Effects of Inlet Pressure on Ignition of Spray Combustion - Jian Chen; Jianzhong Li; Li Yuan (International Journal of Aerospace Engineering)
To evaluate the effects of inlet pressure on the ignition process of spray combustion, the images of the ignition process were recorded and the outlet temperatures were measured under inlet pressure of 0.04–0.16 MPa. The initial flame formation and flame propagation and the effects of the inlet pressure on the initial flame formation were observed. A variation of outlet temperature, flame propagation, initial time of outlet temperature rise, time of maximum temperature rise, and temperature rise rate was investigated. With increasing inlet pressure, the time of initial flame formation and time of maximum area growth rate of flame decrease and the centroid location move radially. The radial distances of the initial flame centroid gradually increased by about 13%, 5%, 6%, 12%, 57%, and 24%. The trace of flame centroid is determined from the distribution of fuel and is related to the initial SMD of the atomizer. The maximum temperature rise and temperature rise rate are determined by the rate of flame chemical reaction, rate of large drop evaporation, and fuel/air ratio. With increasing inlet pressure, the maximum temperature rise increased by 50%, 58%, 12%, 11%, and −9%, respectively. Meanwhile, the rate of the temperature rise increased by about 47%, 54%, 11%, 11%, and −7%, respectively.